The Effect of 9/11 on Immigrants' Ethnic Identity and Employment: Evidence from Germany - Isaure Delaporte (Global Labor Organization (GLO), 2019)
A growing concern in Western countries is the fact that immigrants might adopt oppositional identities. Although identity is expected to affect the economic outcomes of immigrants, little is known about the factors that in uence the identity choice of the migrants and thus, their employment outcomes. This study investigates the effect of the 9/11 terrorist attacks on the process of identity formation and the employment outcomes of Turkish immigrants in Germany. Using longitudinal data from the German Socio-Economic Panel, this study relies on a difference-in-differences strategy to compare the outcomes of Turks with non-Turks before and after the attacks. The results show that Turks have adopted more extreme identities after 9/11 compared to non-Turks: they are more likely to feel completely German; they are less likely to feel in some respects Turkish whereas they are more likely to feel mostly Turkish. There is no significant impact of the 9/11 terrorist attacks on the Turks' employment outcomes relative to non-Turks.
Keywords: J15; J71; Z13; 330; Immigrant; Integration; Ethnic Identity; Employment; Terrorism; Difference-in-Differences Estimation